Tác động của tiêu thụ điện đến lượng khí thải CO2 ở Việt Nam: Đối xứng hay bất đối xứng? - Bùi Hoàng, Ngọc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2020)
The quality of the environment is an interesting topic, which has been attended by the Government and residents. The main aim of the study is to investigate the existence of the asymmetric effect of electricity consumption on CO2 emissions in Vietnam during the 1971-2017 period. By applying Non-linear Autoregressive Distributed Lag approach (NARDL) proposed by Shin et al. (2014), the empirical results reveal that there is an asymmetric effect of electricity consumption on CO2 emissions in the short-run, but this effect is asymmetric in the long-run. The new finding of our analysis contributes to the literature and practical implications.